ILL-POSEDNESS AND STABILITY ESTIMATE FOR THE HEAT EQUATION BACKWARD IN TIME WITH DIRICHLET AND INTEGRAL BOUNDARY CONDITIONS - Nguyen Van Duc; Phan Hoai Linh (Tạp chí Khoa học)
In this paper, we first prove that the heat equation backward in time with Dirichlet and integral boundary conditions is an ill- posed problem. Then, we establish a stability estimate of Hölder type for this ill-posed problem.